Penerapan Strategi Promosi Wisata Melalui Video Cinematic Untuk Meningkatkan Daya Tarik Wisatawan Pasca Pandemi Covid-19 (Studi Kasus: Pantai Teluk Asmara, Malang) - Dirgabangsa, Maulana Arlando; Wahono, Budi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the effectiveness of tourism promotion strategies through cinematic video in enhancing tourist attraction after the COVID-19 pandemic, with a case study at Teluk Asmara Beach, Malang Regency. The research uses a descriptive qualitative approach and a case study method, with data collection techniques including observation, interviews, and documentation. The results show that cinematic video promotion has a significant impact on increasing tourist visits, shaping a strong destination image, and strengthening the local community's economy. This strategy is considered highly effective in supporting the recovery of the tourism sector through digital media. Keywords: Promotion Strategy, Cinematic Video, Tourist Attraction, Digital Tourism, Post-Pandemic.